Survival of Left-to-Right Shunt Repair in Children with Pulmonary Arterial Hypertension at a Tertiary Hospital in a Low-to-Middle-Income Country. Issue 1 (21st April 2021) - Arafuri, Nadya; Murni, Indah K.; Idris, Nikmah S.; Uiterwaal, Cuno S. P. M.; Savitri, Ary I.; Nugroho, Sasmito; Noormanto, Noormanto
Background: In low-to-middle-income countries, repair of the left-to-right shunts congenital heart disease (CHD) are often done with existing pulmonary arterial hypertension (PAH). Long-term outcomes data of this condition in either low-to-middle or high-income countries are limited. We conducted a study to evaluate the outcomes of children with PAH related to left-to-right shunt CHD who underwent surgical or transcatheter repair. Methods: All cases of PAH related to left-to-right shunt CHD repairs from 2015–2018 were retrospectively reviewed with additional new patients who underwent repair within our study period (2019–2020). Cases with complex congenital heart disease and incomplete hemodynamic echocardiography or catheterization measurements were excluded. Kaplan-Meier curves, log-rank test, Cox regression with Firth's correction and restricted mean survival time were used for survival analysis. Results: Of the 118 patients, 103 patients were enrolled and 15 patients were excluded due to complex congenital heart disease and missing hemodynamic measurements prior to repair. Overall, median age at intervention was 44 months, mPAP mean was 43.17 ± 16.05 mmHg and Pulmonary Vascular Resistance index (PVRi) mean was 2.84 ± 2.09 (WU.m 2 ). Nine patients died after repair. The survival rate for patients with PAH-CHD at 1 day, 30 days and 1400 days (4 years) was 96.1%, 92.1%, and 91.0% respectively. Patients with persisting PAH after correction had –476.1 days (95% confidence interval [CI]: –714.4, –237, 8) shorter survival over 4 years of follow up compared to patients with reversed PAH. PVRi was found to be the influencing covariate of the difference of restricted mean survival time between these groups. Conclusion: In low-to-middle income settings, with accurate PAH reversibility assessment prior to intervention, repair of left-to-right shunt CHD with existing PAH in children has a favourable outcome. Inferior survival is found in patients with persistence of PAH. PVRi at baseline predicts between-group survival difference.